Interpreting a Fish Food Package Label - Frank A. Chapman; Richard Miles (EDIS)
FA159, a 6-page fact sheet by Frank Chapman and Richard Miles, provides farmers and pet owners a guide to interpreting the information on fish food labels. Includes additional sources of information. Published by the UF Program in Fisheries and Aquatic Sciences, December 2009.